Anti-diabetic and lipid-lowering effects of drimane sesquiterpenoids isolated from Zygogynum pancheri. (1st October 2020) - Belhadj, Sahla; Keskes, Henda; Apel, Cécile; Roussi, Fanny; Litaudon, Marc; Hentati, Olfa; Allouche, Noureddine
Abstract: Recently, it has been shown that drimane-type sesquiterpenoids isolated from Zygogynum pancheri, a species native to New Caledonia, possessed significant α-amylase inhibitory activities. To further explore their antidiabetic potential, we investigated the effect of 1β- O -( E -cinnamoyl)-6α-hydroxy-9 epi -polygodial (D) and 1β- E - O - p -methoxycinnamoyl-bemadienolide (L), two of the most active compounds of the series, on diabetic model rats. Compounds D and L (2 mg kg/day) were daily and orally administrated for 30 days to streptozotocin (STZ) (150 mg/kg) induced male diabetic Wistar rats. Animals were allocated into five groups of six rats. Comparatively to diabetic rats, treatments with D and L compounds were able to significantly ( P < 0.05) decrease Fasting Blood Glucose (FBG) (70.15%, 71.02%), serum total cholesterol (46.27% and 39.38%), triglycerides (56.60% and 58.15%), creatinine (37.31% and 36.49%) and uric acid levels (67.76% and 69.68%), respectively. Compounds D and L also restored the altered plasma enzyme (aspartate aminotransferase, AST (47.83% and 43.20%), alanine aminotransferase, ALT (49.76% and 48.35%, alkaline phosphatase, ALP (72.78% and 73.21%)) and lactate dehydrogenase, LDH (47.95% and 53.93%) levels to near normal, respectively. Administration of Glymepiride, significantly ( p < 0.05) reduced FBG (73.94%) in STZ induced diabetic rats. Additionally, the compounds D and L exhibited inhibitory effects in vivo on lipase activity of diabetic rats (54.83% and 52.25%), respectively. The outcomes of this study suggested that these two drimanes could be considered as efficient hypoglycemic, hypolipidemic and antiobesity agents for diabetes management and its complications. Graphical abstract: Image 1 Highlights: Drimane sesquiterpenoids significantly inhibited in vitro α-amylase and lipase activities in vivo at a dose 2 mg/kg bw. Drimane sesquiterpenoids lowered glycemia. Drimane sesquiterpenoids reduced the ALT, AST and LDH activities after treatment of diabetic rats. Sections of pancreas, liver and kidney showed the beneficial effects of drimane sesquiterpenoids on diabetic rats.